Evaluation of the Service Life Ratio of Geogrid-Reinforced Flexible Pavement Based on Rutting and Fatigue Criteria (OODBODHAN, 2025)
This study evaluates the Service Life Ratio (SLR) of geogrid-reinforced pavement based on rutting and fatigue criteria, focusing on the Arughat–Okhale Road section of the Mid-Hill Highway in Nepal. Two demonstration sites were established at chainages 1+700m and 1+800m from the Budigandaki Bridge, located at the Dhading–Gorkha district border. The first site consists of a pavement structure without geogrid reinforcement, while the second includes a geogrid placed at the mid-base thickness of the pavement. To assess the performance and effectiveness of the geogrid reinforcement, earth pressure cells, strain gauges, and moisture sensors were installed at the mid-base level, and data were collected regularly over time. The evaluation considers an Equivalent Standard Axle Load (ESAL) of 80 kN for single axle loading. Numerical analysis using 3D finite element modeling in PLAXIS was conducted to assess pavement responses and failure mechanisms. The results indicate that for subgrade California Bearing Ratio (CBR) values ranging from 5% to 9%, rutting is the dominant failure mechanism. However, for CBR values exceeding 9%, fatigue failure becomes the governing criterion. Findings show that the inclusion of geogrid reinforcement significantly enhances pavement performance. The calculated Service Life Ratio (SLR) varies between 2.0 and 1.1 under rutting failure conditions, and between 1.0 and 1.3 under fatigue failure scenarios, depending on subgrade strength. These results suggest that geogrid reinforcement is particularly effective in weak subgrade conditions, contributing to extended pavement life and improved load distribution. This study provides valuable insights into the application of geogrids in flexible pavement design and offers guidance for prioritizing road repair and maintenance strategies.